2020
DOI: 10.1136/bmjdrc-2019-000912
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, control, and treatment of diabetes, hypertension, and high cholesterol in the Amish

Abstract: BackgroundThe burden of diabetes and cardiovascular risk is not uniform across the USA, with much of this disparity tracking differences in socioeconomic status, cultural practices and lifestyle. To further evaluate disparities in these disorders, we assessed the prevalence of diabetes, hypertension, and hypercholesterolemia in an Old Order Amish community that is characterized by distinctive sociocultural practices that include a very cohesive social structure and limited use of modern technologies and medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…This study was based on 6136 Amish individuals from Lancaster, PA over 18 years of age and who were recruited through prior community‐wide studies conducted over the past 20 years (He et al, 2020; Xu et al, 2017). Study subjects had previously filled out detailed surveys regarding their prior pregnancy and reproductive histories including number of pregnancies, number of children, birth date of each child, number of stillbirths, and number of miscarriages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was based on 6136 Amish individuals from Lancaster, PA over 18 years of age and who were recruited through prior community‐wide studies conducted over the past 20 years (He et al, 2020; Xu et al, 2017). Study subjects had previously filled out detailed surveys regarding their prior pregnancy and reproductive histories including number of pregnancies, number of children, birth date of each child, number of stillbirths, and number of miscarriages.…”
Section: Methodsmentioning
confidence: 99%
“…Through our long‐standing population health studies in the Lancaster Amish (He et al, 2020; Hsueh et al, 2000; Mitchell et al, 2008; Streeten et al, 2003), we retrospectively identified 1824 couple pairs in whom we had performed exome sequencing (ES) and obtained detailed information about pregnancy outcomes. In this study, we evaluate the impact of known highly penetrant recessive variants (Crowgey et al, 2019) on reproductive outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes was defined as self-reported diabetes (or reported use of anti-hyperglycemic medications), or glycol hemoglobin ≥6.5% or measuring fasting glucose ≥126 mg/dL [ 36 ]. Hypertension was defined as self-reported hypertension (or reported use of anti-hypertensive medications) or measured systolic blood pressure ≥140 mmHg or diastolic blood pressure ≥90 mmHg [ 36 ]. High cholesterol was defined as the ratio of total cholesterol to HDL of >5.9 [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes was defined that reported: (1) self-reported diabetes; (2) the use of anti-hyperglycemic agents; (3)measured fasting plasma glucose ≥ 126 mg/dL; (4) 2-h plasma glucose ≥ 200 mg/dL during a 75-g oral glucose tolerance test; (5) glycolhemoglobin ≥ 6.5% (27). And hypertension was defined as people who: (1) self-reported hypertension; (2) reported use of antihypertensive agents; (3) measured systolic blood pressure ≥ 140 mmHg; (4)diastolic blood pressure ≥ 90 mmHg (27). High cholesterol levels were defined as the total-to-HDL cholesterol ratio was more than 5.9 (27).…”
Section: Assessments Of Other Variablesmentioning
confidence: 99%
“…And hypertension was defined as people who: (1) self-reported hypertension; (2) reported use of antihypertensive agents; (3) measured systolic blood pressure ≥ 140 mmHg; (4)diastolic blood pressure ≥ 90 mmHg (27). High cholesterol levels were defined as the total-to-HDL cholesterol ratio was more than 5.9 (27). And participants were considered to have a history of cardiovascular disease if they reported ever being told they had any of the following conditions by a health care provider: congestive heart failure, coronary heart disease, angina pectoris, heart attack, or stroke (28).…”
Section: Assessments Of Other Variablesmentioning
confidence: 99%